A megaproject rises in East Africa - Wanjohi Kabukuru (Africa Renewal, 2016)
A distinctive, glass-panelled multi-storey building with tall stone arches stands out in the bushes of Magogoni in Kenya’s historic coastal town of Lamu. It is the headquarters of a 25 billion infrastructure project—the Lamu Port South Sudan Ethiopia Transport (LAPSSET) Corridor— which will link Kenya with Ethiopia, Uganda and South Sudan.